Oral Health-Related Quality of Life among children ages 14-16 in Diliman Preparatory School for AY 2016-2017 - Cadavez, Michelle June B.; Ching, Ezra Emmanuel B.; Sia, Sean Benson T.; Medina, Vicente, III, O., Faculty co-author and Adviser
INTRODUCTION: It is important to determine the correlation of oral health status of adolescents and their oral health-related quality of life (OHRQoL) because it is during this stage of their life when they are more susceptible to dental caries experience (Moynihan & Petersen, 2004). One method of measuring OHRQoL is the Child Oral Health Impact Profile Short Form or COHIP-SF19 (Broder et al, 2012). This study aims to determine the correlation between oral health status and quality of life among 14-16 years old in Diliman Preparatory School.
METHODS: Seventy-three high school children aged 14-16 years old enrolled in a private school participated in the study. The participants were asked to answer the COHIP-SF19 questionnaire to determine their OHRQoL. The school dental records were reviewed to determine their oral health status by calculating their number of decayed, missing and filled teeth (DMFT). To determine the correlation of their oral health status and OHRQoL, Spearman?s rank correlation was used with an 80% confidence level.
RESULTS: Oral Health Well-being, Functional Well-being, Social/Emotional Well-being and School Environment domains negatively correlated with DMFT index. Only self-image exhibited a positive but not significant correlation with oral health status. Their oral health status and quality of life had very weak inverse correlation and it was not significant.
CONCLUSIONS: Based on the participant?s mean COHIP-SF19 and DMFT scores, their oral health status is not significantly correlated with their quality of life.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health; Quality of life--Philippines.; Decayed, missing and fillet teeth (DMFT).